Porous fiber aerogel as well as preparation method and application thereof in protein adsorption separation
The preparation of porous fiber aerogels by cross-linking alginate fiber and sodium alginate has solved the problems of low efficiency and high cost of protein separation and purification in the prior art, and achieved efficient and low-cost protein adsorption and separation effects.
Patent Information
- Application Number
- CN202411491451.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-03-14
AI Technical Summary
The existing protein separation and purification technology is inefficient and costly, and the adsorption separation medium of microparticles is large in size and small in pore size structure, resulting in slow protein mass transfer, low processing flux, large resistance, and large energy consumption.
Porous fiber aerogel is formed by cross-linking of alginate fibers and sodium alginate through calcium ion, forming a vertical uniform pore structure and rich hydroxyl functional groups, improving protein adsorption capacity.
It realizes efficient protein adsorption and separation, reduces circulation resistance, improves water treatment flux, reduces production costs, and improves protein production efficiency.
Smart Images

Figure CN119613822A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of protein separation and purification, and in particular relates to a porous fiber aerogel and a preparation method thereof and application thereof in protein separation and purification. Background Art
[0002] Protein products are widely needed in the food industry, life science research and biomedicine. In its production process, separation and purification are the most critical steps, which determine the purity and biological activity of protein products and account for more than 80% of the production cost. Therefore, efficient and low-cost separation and purification technology is the key to the development of many industries.
[0003] At present, the commonly used protein separation and purification methods in engineering, such as precipitation, centrifugation, extraction, electrophoresis, membrane separation, etc., are either expensive, or have low separation accuracy, or are prone to contamination, and are not ideal extraction methods. At present, extensive research focuses on adsorption separation methods to achieve efficient, universal and sustainable protein separation. However, the current research on protein adsorption separation materials still faces huge development bottlenecks. This is mainly because the currently widely used micron particle protein adsorption separation media are large in size (20-200μm) and have a small pore structure (<100nm), which leads to slow protein mass transfer, low processing flux, high resistance, high energy consumption and other problems. Therefore, designing protein adsorption separation materials with high adsorption capacity, high processing flux and low resistance pressure drop is the focus and hot spot of current research in the field of protein separation and purification.
[0004] Alginate is a natural polysaccharide composed of β-D-mannuronic acid and α-L-guluronic acid obtained from marine brown algae. Due to its wide source and rich active functional groups such as hydroxyl and carboxyl groups in the molecular chain, especially its strong negative charge on the surface, it can provide abundant binding sites for positively charged proteins such as lysozyme, showing excellent protein adsorption and separation potential. Alginate can form a stable gel with an "egg box" structure in the presence of divalent cations such as calcium, but it has the problems of dense structure, lack of pore structure, small specific surface area and limited adsorption sites. Composite or cross-linking with other materials such as cellulose fiber, chitosan, silk protein, polyethylene glycol, etc. is an effective method to regulate the pore structure of alginate adsorbent, but the composite of the above materials with alginate will occupy some of its adsorption sites, significantly reducing the adsorption capacity of alginate itself. Therefore, it is imperative to develop an alternative pore structure engineering strategy to fully expose the protein adsorption sites on the surface of alginate gel while avoiding the occupation of adsorption sites by other materials. Alginate fibers have a high specific surface area due to their high aspect ratio, which can provide more abundant sites for protein adsorption. The use of alginate fibers and alginate gel to construct composite gel materials is expected to open up a new path for the construction of high-performance protein adsorption and separation materials, but the relevant methods have not yet been reported. Summary of the invention
[0005] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. In order to solve the problem of high cost and efficiency of existing protein separation and purification, the present invention provides a porous fiber aerogel and a preparation method and use in protein separation and purification. The provided porous fiber aerogel is composed of alginate fiber and sodium alginate cross-linked by calcium ions. Alginate fiber and sodium alginate both contain a large number of hydroxyl functional groups, which can provide a large number of adsorption sites for positively charged proteins, and under the action of hydrogen bonds, the adsorption capacity for positively charged proteins is further enhanced. Moreover, the formed porous fiber aerogel also has a vertical pore network structure, which can reduce the flow resistance, increase the water treatment flux, avoid clogging and other problems, thereby realizing the reduction of protein production costs and the improvement of protein production efficiency by constructing a low-cost but high-performance protein adsorption and separation material.
[0006] Specifically, the present invention provides the following technical solutions:
[0007] In a first aspect, the present invention provides a porous fiber aerogel, wherein the porous fiber aerogel comprises alginate fibers and sodium alginate, wherein the alginate fibers and sodium alginate are mixed, directional frozen-formed by liquid nitrogen, and cross-linked by calcium ions to form a vertically uniform pore structure.
[0008] The porous fiber aerogel provided includes alginate fiber and sodium alginate, wherein the alginate fiber is used as a scaffold and the sodium alginate is used as an adhesive. The two are directional frozen by liquid nitrogen to form a vertical uniform pore structure, and the inner and outer walls of the pores are rich in pore structures, so that it has a high specific surface area. Its surface carries a large number of carboxyl functional groups, which can bind a large number of positively charged proteins through electrostatic and functional group effects. The porous fiber aerogel is placed in a protein mixed solution to be purified, and the positively charged protein can be effectively adsorbed in the porous fiber aerogel to achieve protein separation and purification.
[0009] According to an embodiment of the present invention, the provided porous fiber aerogel may further include the following technical features:
[0010] In some embodiments of the present invention, the mass ratio of the alginate fiber to the sodium alginate is 2.5-10:97.5-90. According to a preferred embodiment, the mass ratio of the alginate fiber to the sodium alginate is 5:95.
[0011] In some embodiments of the present invention, the alginate fiber is prepared by wet spinning.
[0012] A second aspect of the present invention provides a method for preparing a porous fiber aerogel, comprising:
[0013] Providing an alginate fiber solution and a sodium alginate solution, and uniformly dispersing the alginate fiber solution in the sodium alginate solution to obtain a precursor solution;
[0014] The precursor solution is subjected to a first freezing and a first vacuum drying process to obtain an uncrosslinked aerogel;
[0015] The uncrosslinked aerogel is crosslinked with calcium ions, and subjected to a second freezing and a second vacuum drying process to obtain the porous fiber aerogel.
[0016] The porous fiber aerogel provided is bonded by alginate fibers and sodium alginate to have a more stable structure, and is then prepared by liquid nitrogen directional freezing to form a vertically uniform pore structure, which makes it easy for the liquid to be treated to flow, improves the treatment flux, reduces the treatment pressure drop, and improves the protein separation and purification efficiency.
[0017] According to an embodiment of the present invention, the method for preparing the porous fiber aerogel described above may further include the following technical features:
[0018] In some embodiments of the present invention, the mass concentration of the alginate fiber solution is 0.5wt% to 5wt%;
[0019] The concentration of the sodium alginate solution is 0.5wt% to 5wt%;
[0020] The calcium ion is a calcium chloride solution, and the concentration of the calcium chloride solution is 0.2 mol / L to 0.5 mol / L.
[0021] In some embodiments of the present invention, the first vacuum drying process and the second vacuum drying process are each independently selected from vacuum drying processes performed at a pressure less than 30 Pa.
[0022] In some embodiments of the present invention, the first freezing is a liquid nitrogen directional freezing process, wherein the temperature of the liquid nitrogen directional freezing process is about -190 degrees Celsius.
[0023] In some embodiments of the present invention, the second freezing is performed at -20 to -60 degrees Celsius. The freezing process can be performed in a refrigerator during the operation.
[0024] The third aspect of the present invention provides the use of the porous fiber aerogel described in the first aspect or the porous fiber aerogel obtained according to the preparation method described in the second aspect in the field of protein adsorption separation or toxin separation.
[0025] A fourth aspect of the present invention provides a method for separating a target protein in a sample, comprising:
[0026] Adding porous fiber aerogel to the sample for adsorption treatment, wherein the porous fiber aerogel is the porous fiber aerogel described in the first aspect or the porous fiber aerogel obtained according to the preparation method described in the second aspect;
[0027] The target protein in the sample is separated and obtained.
[0028] In some embodiments of the present invention, the target protein is selected from at least one of lysozyme, hemoglobin, whey protein, cytochrome C, bromelain, and papain.
[0029] A fifth aspect of the present invention provides a method for purifying a target protein, comprising:
[0030] Adding a porous fiber aerogel to a sample containing a target protein for adsorption treatment, wherein the porous fiber aerogel is the porous fiber aerogel described in any one of the first aspect or the porous fiber aerogel obtained by the preparation method described in any one of the second aspect;
[0031] Separating and removing impurities from the sample containing the target protein to obtain a porous fiber aerogel adsorbed with the target protein;
[0032] The porous fiber aerogel adsorbed with the target protein is subjected to desorption treatment to obtain the target protein.
[0033] The sample containing the target protein mentioned is an acidic sample solution, for example, the pH value is 2 to 6.5, preferably 3 to 4. According to an embodiment of the present invention, when performing a desorption treatment, a calcium chloride solution can be used as an eluent, and the porous fiber aerogel adsorbed with the target protein can be placed in the eluent, and an oscillation treatment is performed to perform a desorption treatment. Specifically, the eluent used can be a 0.1M to 0.2M calcium chloride solution. A shaking table can be used for oscillation treatment, for example, a shaking table oscillation treatment at a speed of 100 to 200 rpm (for example, 150 rpm). Then, by adjusting the pH to reach the isoelectric point of the target protein, the target protein is precipitated, and the target protein is separated and obtained.
[0034] According to an embodiment of the present invention, the target protein carries a positive charge.
[0035] A sixth aspect of the present invention provides a method for removing toxins from a sample, comprising:
[0036] Adding porous fiber aerogel to a sample containing toxins for adsorption treatment to obtain porous fiber aerogel adsorbed with toxins; the porous fiber aerogel is the porous fiber aerogel described in any one of the first aspect or the porous fiber aerogel obtained by the preparation method described in any one of the second aspect;
[0037] Separation and removal of toxin-adsorbed porous fiber aerogels.
[0038] The toxins mentioned have a positive charge, including but not limited to urea, uric acid, creatinine, etc.
[0039] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0040] (1) The porous fiber aerogel provided by the present invention makes full use of its own components. The structures all contain abundant hydroxyl functional groups, and the exposed sites are protein adsorption sites, which greatly improve the protein adsorption capacity. It can also be used to adsorb charged toxins, thereby being used to remove toxins.
[0041] (2) The provided aerogel has a vertically uniform pore structure, which improves the flux of liquid flowing through the aerogel, and a large number of pore structures are also distributed on the wall surface, which greatly increases the specific surface area and improves the protein adsorption capacity.
[0042] (3) The raw materials required for the preparation of aerogels are abundant and low in cost. The preparation method is simple and does not require expensive equipment. The preparation process is safe and pollution-free. This technology has a low threshold for use and good effects. It can be used in a wide range of protein separation and purification processes, saving protein production costs and improving protein production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 The figure is a schematic diagram of the preparation process of the porous fiber aerogel provided according to an embodiment of the present invention.
[0044] Figure 2 The adsorption capacity of different porous fiber aerogels provided according to the embodiments of the present invention.
[0045] Figure 3 This is a graph showing the effect of the dosage of the porous fiber aerogel provided in an embodiment of the present invention on the adsorption capacity.
[0046] Figure 4 The porous fiber aerogel provided by an embodiment of the present invention has an effect on the adsorption of proteins in solutions with different pH values.
[0047] Figure 5 The results of the change of the adsorption capacity of the porous fiber aerogel with the increase of the lysozyme concentration provided by the embodiment of the present invention are as follows.
[0048] Figure 6 The adsorption kinetics results of the porous fiber aerogel adsorption amount varying with time according to the embodiments of the present invention are shown.
[0049] Figure 7This figure shows the effect of different cycle times on the protein adsorption capacity of the porous fiber aerogel provided by an embodiment of the present invention.
[0050] Figure 8 The following are the scanning electron microscope observation results of the porous fiber aerogel provided according to the embodiment of the present invention.
[0051] Fig. 9 The porous fiber aerogels of different shapes and sizes are prepared according to the embodiments of the present invention.
[0052] Fig.10 This is the result of total lysozyme content provided in different eluents provided in the examples of the present invention.
[0053] Fig.11 It is a diagram of electrophoresis results provided according to an embodiment of the present invention. DETAILED DESCRIPTION
[0054] Embodiments of the present invention are described in detail below. Examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0055] The present invention provides a porous fiber aerogel, wherein the porous fiber aerogel is mainly made of alginate fiber and sodium alginate as raw materials, the alginate fiber is bonded by a sodium alginate solution, the structure is more stable, and then the alginate fiber is directional frozen by liquid nitrogen, cross-linked by calcium ions, and then frozen to form a vertical uniform pore structure. The provided porous fiber aerogel is placed in a protein mixed solution to be purified, and the positively charged protein can be effectively adsorbed in the porous fiber aerogel, thereby achieving protein separation and purification.
[0056] During the research process, we tried to prepare porous fiber aerogels by compounding a variety of raw materials, but the effect was not good. For example, porous fiber aerogels were prepared using cellulose acetate and sodium alginate as raw materials, but the adsorption effect of the prepared porous fiber aerogels was not good, and the adsorption capacity was only about 70 mg / g. The porous fiber aerogel composed of alginate-based materials has abundant surface carboxyl active sites, and combined with hydrogen bonding, it has ultra-high positively charged protein adsorption capacity. Combined with the high specific surface area of the fiber, the protein adsorption sites are greatly increased, and it has an ultra-high protein adsorption capacity of more than 8.35 g / g.
[0057] Wet spinning is a spinning method in which a fiber-forming polymer is dissolved in an appropriate solvent to prepare a solution with a certain viscosity and good spinnability, and then extruded through a spinneret to form a thin stream, which enters a coagulation bath to form a fiber. The alginate fiber used is obtained by wet spinning. The alginate fiber obtained by wet spinning is to put a sodium alginate solution into a syringe and extrude it through a spinneret to form a thin stream, which enters a coagulation bath (usually a calcium chloride solution), and the sodium alginate reacts with the calcium ions in the coagulation bath to form a calcium alginate gel fiber. The coagulated fiber is stretched to a certain proportion to improve its strength and orientation. The residual coagulant and unreacted sodium alginate in the fiber are washed away. The wet fiber is dried to obtain the final dry fiber. The alginate fiber can be obtained commercially or prepared by yourself. The sodium alginate powder used can be obtained commercially.
[0058] In the process of directional freezing molding using liquid nitrogen, different shapes can be prepared to form porous fiber aerogels of different shapes to adapt to different uses.
[0059] The porous fiber aerogel provided by the present invention has certain mechanical properties, can stably exist in a fluid, and has certain compression and memory deformation capabilities.
[0060] The provided porous fiber aerogel can be used to adsorb positively charged proteins or toxins under acidic conditions, thereby being used for protein adsorption and separation or toxin separation and removal. The mentioned proteins include but are not limited to lysozyme, hemoglobin, whey protein, cytochrome C, bromelain, papain, etc., and the mentioned toxins include but are not limited to urea, uric acid or creatinine, etc.
[0061] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention can also be implemented in other ways different from those described herein, and therefore, the protection scope of the present invention is not limited by the specific embodiments disclosed below.
[0062] If not specified, the alginate fibers used were commercially available wet-spun alginate fibers, the sodium alginate used was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., calcium chloride was purchased from Sinopharm Group Pharmaceutical Co., Ltd., lysozyme was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., and PBS buffer was purchased from Lanjieke Technology Co., Ltd. All aqueous solutions were prepared with deionized water (resistivity = 18.25 MΩ*cm).
[0063] Example 1
[0064] Example 1 prepared porous fiber aerogels with different proportions, including the following steps:
[0065] A 1 wt% alginate fiber solution was prepared and processed with a soybean milk machine for 10 min to completely disperse the fibers; a 1 wt% sodium alginate solution was prepared and then mixed with the alginate fiber solution in different mass ratios to obtain a uniform precursor solution (reference Figure 2 As shown, the mass fractions of alginate fibers are: 0, 2.5%, 5%, 10%, 20%, 40%, 50%, 60%, 80%, 90%, 100%);
[0066] The precursor solution is poured into a mold, and the mold is formed by liquid nitrogen directional freezing. The resulting frozen block is placed in a freeze dryer and vacuum dried at a pressure of less than 30 Pa to prepare an uncrosslinked aerogel.
[0067] The uncross-linked aerogel was immersed in a 0.3M calcium chloride solution for 20 minutes and then repeatedly rinsed with pure water to remove the calcium chloride remaining on the surface of the aerogel. The aerogel was placed in a -60°C refrigerator and fully frozen. It was then placed in a freeze dryer again and vacuum dried at a pressure of less than 30 Pa to finally prepare a cross-linked porous fiber aerogel.
[0068] Example 2
[0069] Example 2 The protein adsorption performance of the porous fiber aerogels with different proportions prepared in Example 1 was tested.
[0070] The porous fiber aerogel prepared by mixing the sodium alginate solution and the alginate fiber solution in different proportions as described in Example 1 was taken as an example. Lysozyme was used as a template protein to evaluate the protein adsorption performance of the aerogel.
[0071] The pH of commercially available phosphate buffered saline was adjusted to 3 by hydrochloric acid and sodium hydroxide, and then 200 mg of lysozyme was added to 100 ml of PBS buffer solution under slow stirring. 80 mg of porous fiber aerogel was taken and immersed in a conical flask containing the above lysozyme solution. After shaking at a speed of 150 rpm for a certain period of time, 2 ml of solution sample was taken. The concentration of the lysozyme solution before and after adsorption was tested by using an ultraviolet-visible spectrophotometer (Tsushima UV-1601PC) to detect the change in the absorbance intensity of the obtained solution at a wavelength of 278 nm, and the lysozyme adsorption capacity of the porous fiber aerogel was calculated based on the concentration difference of the protein solution before and after adsorption.
[0072] The following formula is used to calculate the aerogel protein adsorption capacity:
[0073] q e=V(C0-C e ) / m
[0074] Among them, q e is the adsorption capacity at equilibrium, V is the volume of the protein solution, C0 and Ce are the initial concentration of lysozyme and the concentration when dynamic adsorption equilibrium is reached, and m is the amount of adsorbent added.
[0075] The experimental results are as follows Figure 2 As shown: With the increase of the proportion of alginate fiber solution in the aerogel preparation precursor solution, the protein adsorption performance of the obtained aerogel first increases and then decreases. After reaching a ratio of 5:5, it shows a trend of first increasing and then decreasing. It is worth noting that under the condition of 80mg porous fiber aerogel dosage, when only 5% alginate fiber is added, the protein adsorption performance is the best, reaching 2.4g / g. The interaction between the change of fiber content and the adsorption effect fully reflects the structure-activity relationship that the aerogel fiber structure determines the protein adsorption performance. Among them, when the mass fraction of alginate fiber is 5%, the prepared porous fiber aerogel has the best adsorption performance. On this basis, the following research is further carried out.
[0076] Example 3
[0077] Example 3 The effect of the dosage of aerogel (taking the aerogel prepared with a mass fraction of 5% alginate fiber as described in Example 2 above as an example) on its maximum adsorption capacity was studied in the same 100 ml, 2 mg / ml lysozyme solution as mentioned above, with the solution pH = 3.
[0078] The experimental results are as follows Figure 3 As shown, the experimental results show that the protein adsorption performance of the porous fiber aerogel changes with the change of the aerogel dosage. When the dosage is greater than 20 mg, the aerogel adsorption capacity decreases with the increase of the dosage. When the dosage is less than 20 mg, the aerogel adsorption capacity increases with the increase of the dosage. When the dosage is 20 mg, the aerogel has the maximum adsorption capacity, that is, the best protein adsorption performance of 8.35 g / g is achieved. The reason may be that when the aerogel dosage is greater than 20 mg, the adsorption sites on the aerogel surface are not fully occupied by lysozyme, so its adsorption potential is not fully utilized. When the dosage is less than 20 mg, the adsorption sites are insufficient, and there is a competitive relationship between lysozymes, resulting in failure to achieve the best adsorption performance. Therefore, the following studies all use an aerogel dosage of 20 mg.
[0079] Example 4
[0080] Example 4 further studies the effect of solution properties on protein adsorption in porous fiber aerogels.
[0081] The pH value of commercially available phosphate buffer solution was adjusted to between 2 and 8 by hydrochloric acid and sodium hydroxide, and lysozyme solutions of different concentrations of 0-4 mg / ml were prepared. Taking the aerogel prepared with the best adsorption performance and containing 5% by mass of alginate fiber as an example, the lysozyme adsorption performance was determined by referring to the above method.
[0082] The experimental results are as follows Figure 4 As shown in the figure, the experimental results show that the protein adsorption performance of the porous fiber aerogel increases with the increase of solution pH at pH 2-3, reaches a maximum value of 8.35 g / g at pH 3, and then decreases with the increase of pH. However, it still maintains relatively excellent protein adsorption performance in the solution pH range of 2-7, and the adsorption capacity remains above 1.5 g / g.
[0083] like Figure 5 As shown, with the increase of lysozyme concentration in the solution, the adsorption capacity of the porous fiber aerogel increases, and the aerogel with a dosage of 20 mg reaches adsorption equilibrium when the lysozyme concentration is 2 mg / ml.
[0084] Figure 6 The adsorption kinetics results of the aerogel adsorption amount over time under the above optimal conditions are shown.
[0085] Example 5
[0086] Example 5 evaluates the recycling performance of the porous fiber aerogel.
[0087] The reusability of the porous fiber aerogel was evaluated by subjecting it to 10 cycles of protein adsorption-desorption experiments. First, the optimal aerogel mentioned in Example 3 was used for the adsorption experiment. After a sufficient adsorption time, the concentration of the lysozyme solution after adsorption was determined. Subsequently, a 0.1M calcium chloride solution was used as the eluent, and the adsorbed aerogel was transferred to a 50ml calcium chloride solution, which was placed in a 150rpm shaker for desorption. Every 10 minutes, the aerogel was transferred to a new calcium chloride solution, and the above operation was repeated until the absorption peak of lysozyme was not detected in the last eluent. The obtained aerogel was then rinsed with ultrapure water 5 times to remove the residual calcium chloride on the aerogel, and used for subsequent adsorption experiments. The aerogel after desorption treatment was repeatedly used in 10 cycles to measure its recycling performance.
[0088] The experimental results are as follows Figure 7 As shown, the experimental results show that after 5 cycles, the protein adsorption performance of the aerogel decreases by only ≤10%, and after 10 cycles, the protein adsorption performance decreases by only ≤15%, while the protein adsorption capacity of the aerogel is maintained above 6.7g / g, still having excellent protein adsorption performance and good recyclability.
[0089] Example 6
[0090] Example 6 conducts structural characterization and mechanism investigation on the prepared porous fiber aerogel.
[0091] like Figure 8 As shown in the figure, the aerogel morphology was observed by scanning electron microscopy (SEM). The porous fiber aerogel obtained by the present invention showed a 3D skeleton with a combination of large and small pores and a vertically uniform pore structure, and had a super strong adsorption capacity. In addition, alginate fibers and sodium alginate powder are both natural polymer materials with abundant sources, low cost, biosafety, and easy access, allowing the continuous production of aerogels. The good controllability of the preparation process can ensure the possibility of designing aerogels of different shapes and sizes, such as "W", "H", "U", etc. (such as Fig. 9 shown).
[0092] Zeta potential test shows that in the pH range of 2 to 8, the original materials including alginate fiber and sodium alginate powder and the prepared aerogel surface are negatively charged. The isoelectric point of lysozyme is generally between pH 10.5-11.0, and lysozyme is positively charged when the pH is less than 10.5. This indicates that there is an electrostatic effect between the aerogel and lysozyme, which promotes the adsorption performance of the aerogel on lysozyme.
[0093] The compression performance of the aerogel shows that the aerogel has the best mechanical properties when the ratio of alginate fiber to sodium alginate powder is 1:1. It can also maintain a certain shape during 1000 cycles of compression and does not collapse completely. The aerogel exhibits a good memory deformation process in aqueous solution. After kneading it into a ball and putting it in aqueous solution, it can still restore its original shape after a short period of time.
[0094] The investigation of the aerogel adsorption kinetics showed that the aerogel's kinetic adsorption process of lysozyme has a higher fit with the pseudo-second-order kinetic model, indicating that the adsorption of aerogel and lysozyme has a chemical effect in addition to the physical effect. Its isothermal adsorption process is more consistent with the Langmuir monolayer adsorption model, indicating that a monolayer uniform adsorption occurs, further indicating that the aerogel has abundant and easily accessible carboxyl functional groups.
[0095] Example 7
[0096] Example 7: Lysozyme was extracted from egg white using the porous fiber aerogel of the present invention.
[0097] 50 g of egg white stock solution was mixed with 200 ml of phosphate buffer solution (pH=6), and the obtained mixed egg white solution was centrifuged at 10000 rpm for 15 min to finally obtain a clear and transparent egg white solution free of insoluble impurities.
[0098] To further test the extraction ability of porous fiber aerogel for lysozyme in egg white, 60 mg of porous fiber aerogel was placed in 50 ml of treated egg white and continuously shaken on a shaker at 150 rpm for 8 h at room temperature of 25 ° C. The aerogel after lysozyme extraction was then taken out of the egg white solution and rinsed alternately with pH = 6 buffer and deionized water until the protein absorption peak could not be detected at 280 nm in the rinse solution. The aerogel was then immersed in 0.1 M calcium chloride solution and desorbed by shaking on a shaker at 150 rpm. The solution volume used for each desorption cycle was 5 ml and the analysis time was 10 min.
[0099] Then, the lysozyme content in the eluate was detected by UV spectrophotometer at 280 nm, and the quantitative calculation results showed that the total lysozyme content extracted from 10g of original egg white solution by aerogel was 68.7mg ( Fig.10 shown).
[0100] Furthermore, the purity of the protein extract was qualitatively analyzed by SDS-PAGE. In SDS-PAGE electrophoresis, the lysozyme band usually appears at the position of 14.7kD. The egg white solution after aerogel adsorption did not show a lysozyme band at 14.7kD, indicating that the lysozyme in the solution was fully adsorbed on the aerogel; the above-mentioned eluate showed a lysozyme band at 14.7kD, indicating that the lysozyme adsorbed on the aerogel was successfully eluted. Compared with the original egg white solution, the obtained protein eluate only showed a clear electrophoretic band at 14.7kD, which shows that the alginate fiber aerogel can effectively separate and purify lysozyme from egg white, showing good practical application effects (such as Fig.11 shown).
[0101] Although the embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and cannot be understood as limiting the present invention. A person of ordinary skill in the art can change, modify, replace and modify the above embodiments within the scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A porous fiber aerogel, characterized in that: The invention comprises alginate fibers and sodium alginate. The alginate fibers and the sodium alginate are mixed, directional frozen and formed by liquid nitrogen, and cross-linked by calcium ions to form a vertical uniform pore structure.
2. The porous fiber aerogel according to claim 1, characterized in that: The mass ratio of the alginate fiber to the sodium alginate is 2.5-10:97.5-90.
3. The porous fiber aerogel according to claim 1, characterized in that: The alginate fiber is prepared by wet spinning.
4. A method for preparing a porous fiber aerogel, characterized in that: include: Providing an alginate fiber solution and a sodium alginate solution, and uniformly dispersing the alginate fiber solution in the sodium alginate solution to obtain a precursor solution; The precursor solution is subjected to a first freezing and a first vacuum drying process to obtain an uncrosslinked aerogel; The uncrosslinked aerogel is crosslinked with calcium ions, and subjected to a second freezing and a second vacuum drying process to obtain the porous fiber aerogel.
5. The preparation method according to claim 4, characterized in that: The mass concentration of the alginate fiber solution is 0.5wt% to 5wt%; The mass concentration of the sodium alginate solution is 0.5wt% to 5wt%; The calcium ion is a calcium chloride solution, and the concentration of the calcium chloride solution is 0.2 mol / L to 0.5 mol / L.
6. The preparation method according to claim 4, characterized in that: The first vacuum drying process and the second vacuum drying process are each independently selected from vacuum drying processes performed at a pressure of less than 30 Pa; Optionally, the first freezing is a liquid nitrogen directional freezing process; Optionally, the second freezing is a freezing treatment performed at -20 to -60 degrees Celsius.
7. Use of the porous fiber aerogel according to any one of claims 1 to 3 or the porous fiber aerogel obtained by the preparation method according to any one of claims 4 to 6 in the field of protein adsorption separation or toxin separation.
8. A method for separating a target protein from a sample, characterized in that: include: Adding a porous fiber aerogel to the sample for adsorption treatment, wherein the porous fiber aerogel is the porous fiber aerogel according to any one of claims 1 to 3 or the porous fiber aerogel obtained by the preparation method according to any one of claims 4 to 6; Separating and obtaining the target protein in the sample; Optionally, the target protein is selected from at least one of lysozyme, hemoglobin, whey protein, cytochrome C, bromelain and papain.
9. A method for purifying a target protein, characterized in that: include: Adding a porous fiber aerogel to a sample containing a target protein for adsorption treatment, wherein the porous fiber aerogel is the porous fiber aerogel according to any one of claims 1 to 3 or the porous fiber aerogel obtained by the preparation method according to any one of claims 4 to 6; Separating and removing impurities from the sample containing the target protein to obtain a porous fiber aerogel adsorbed with the target protein; Desorbing the porous fiber aerogel adsorbed with the target protein to obtain the target protein; Optionally, the protein of interest is positively charged.
10. A method for removing toxins from a sample, characterized in that: include: Adding porous fiber aerogel to a sample containing toxins for adsorption treatment to obtain porous fiber aerogel adsorbing toxins; The porous fiber aerogel is the porous fiber aerogel according to any one of claims 1 to 3 or the porous fiber aerogel obtained by the preparation method according to any one of claims 4 to 6; Separating and removing porous fiber aerogels with adsorbed toxins; Optionally, the toxin has a positive charge.
Citation Information
Patent Citations
Unidirectional sodium alginate-cellulose fiber aerogel and preparation method thereof
CN116376099A
Fibrous adsorbent of alginic acid, production method of fibrous adsorbent of alginic acid, and adsorption method using fibrous adsorbent
JP2017042689A
Cited By
Hierarchical porous sodium alginate nanofiber aerogel as well as preparation method and application thereof
CN122465210A